Optimization of DC magnetron sputtering deposition process and surface properties of HA-TiO2 film - P. Premphet (2018)
© 2017 Elsevier Ltd. All rights reserved. Hydroxyapatite (HA) and Titanium (Ti) thin film was fabricated by a pulsed DC magnetron sputtering technique. To synthesize a thin film that compatible with bone cell, optimize parameter of the sputtering process and study of the film properties were carried out. The response surface method (RSM) has been applied in this work and there are 3 considering factors: pressure, power level and a distance between target and substrate. The experiment was conducted by a physical property testing to determine young's modulus and layer components. The result showed that the differentiation of components and film thickness were related to a variation of a surface coating time. A structure of the film was performed by Atomic Force Microscope (AFM) and X-ray Photoelectron Spectroscopy (XPS). The analysis showed that HA-TiO2 film was synthesized in sputtering process and the young's modulus of the film was higher value compared to the bone. Finally, the result of biological property testing proved that HA-TiO2 film had a bio-compatible property and UV light affect the TiO2 composition to be a toxic with bone cell.